A corpus-based investigation of noun phrase complexity in the L2 writings of a first-year composition course. Issue 38 (March 2019) - Lan, Ge; Sun, Yachao
Abstract: This study presents frequency and correlation analyses of noun modifiers in L2 student writing, as represented in Purdue University's Corpus and Repository of Writing (Crow). In the study, 79 argumentative papers are extracted from Crow to examine the use of 11 noun modifiers reported in Biber, Gray, and Poonpon (2011). In the frequency analysis, the modifiers used by L2 student writers are compared to those found in academic journal articles. In the correlation analysis, the frequency of each noun modifier is correlated with the students' TOEFL writing scores. The results show that the modifiers, especially phrasal noun modifiers (i.e., nouns as modifiers, prepositional phrases), are used more frequently in academic journal articles than in L2 writing and that the correlation between the modifiers and the students' TOEFL scores is much stronger for basic than for advanced noun modifiers. This suggests that first-year L2 students would benefit from targeted instruction on advanced noun modifiers during academic writing courses.